Optimizing the productivity of vaname shrimp fry (Litopenaeus vannamei) through giving Potassium Nitrate (KNO3) to the cultivation of Skeletonema sp - Handajani, Hany; Zubaidah, Anis; Nailin, Nila Choirun; Purnomo, Hari (Universitas Malikussaleh, 2025)
Skeletonema sp. culture its growth is strongly influenced by the nutrients in the environment where it lives, therefore fertilizer is needed in the culture media to support the availability of both macro and micro nutrients. The purpose of this study was to determine the effect of KNO3 administration on the growth and density of Skeletonema sp. cells. and dosage to obtain the best KNO3 fertilizer. This study used a completely randomized design (CRD), consisting of 4 treatments and 3 replications. KNO3 fertilizer dosage treatments included A (100 ppm), B (200 ppm), C (300 ppm), and control K (500 ppm). Parameters measured were specific growth rate and cell density of Skeletonema sp. The results of the study on density showed that the best treatment was treatment K of 269.5 ᵡ 104 cells/mL, followed by C 300 ppm (203.5 ᵡ 104 cells/mL), B 200 ppm (126.08 ᵡ 104 cells/mL), and A 100 ppm (94.75 ᵡ 104 cells/mL). The average specific growth rate produced in each treatment corresponds to the cell density pattern, namely K (0.434/day); C(0.379/day); B(0.279/day); and A (0.220/day). The application of KNO3 fertilizer with different doses had a significant effect on the growth and density of Skeletonema sp. cells. The higher the KNO3 dose, the higher the growth rate and density of Skeletonema sp cells. high too. Keywords: Fertilizer Dose; Kalium Nitrate; Phytoplankton